Kompresivní zlomeniny thorakolumbální páteře u dětí - Štulík, J; Salavcová, L; Trč, T; Havránek, P; Pešl, T; Barna, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2023)
PURPOSE OF THE STUDY The study aimed to draw up a diagnosis and treatment guidelines for the management of the most common compression fractures of the thoracolumbar spine in children. MATERIAL AND METHODS Between 2015 and 2017, pediatric patients with a thoracolumbar injury aged 0-12 years were followed up in the University Hospital in Motol and the Thomayer University Hospital. The age and gender of the patient, injury etiology, fracture morphology, number of injured vertebrae, functional outcome (VAS and ODI modified for children), and complications were assessed. An X-ray was performed in all patients, in indicated cases also an MRI scan was done, and in more severe cases a CT scan was obtained as well. RESULTS The average vertebral body kyphosis in patients with one injured vertebra was 7.3° (range 1.1°-12.5°). The average vertebral body kyphosis in patients with two injured vertebrae was 5.5° (range 2.1°-12.2°). The average vertebral body kyphosis in patients with more than two injured vertebrae was 3.8° (range 0.2°-11.5°). All patients were treated conservatively in line with the proposed protocol. No complications were observed, no deterioration of the kyphotic shape of the vertebral body was reported, no instability occurred, and no surgical intervention had to be considered. DISCUSSION Pediatric spine injuries are in most cases treated conservatively. Surgical treatment is opted for in 7.5-18% of cases, in dependence on the evaluated group of patients, age of the patients and philosophy of the department concerned. In our group, all patients were treated conservatively. CONCLUSIONS 1. To diagnose F0 fractures, two unenhanced orthogonal view X-rays are indicated, whereas MRI examination is not routinely performed. In F1 fractures, an X-ray is indicated, and an MRI scan is considered based on the age and extent of injury. In F2 and F3 fractures, an X-ray is indicated and subsequently the diagnosis is confirmed by MRI, in F3 fractures also a CT scan is performed. 2. In young children (under 6 years of age), in whom an MRI procedure would require general anaesthesia, MRI is not routinely performed. 3. In F0 fractures, crutches or a brace are not indicated. In F1 fractures, verticalization using crutches or a brace is considered in dependence on the patient's age and extent of injury. In F2 fractures, verticalization using crutches or a brace is indicated. 4. In F3 fractures, surgical treatment is considered, followed by verticalization using crutches or a brace. In case of conservative treatment, the same procedures as in F2 fractures are applied. 5. Long-term bed rest is contraindicated. 6. Duration of spinal load reduction (restriction of sports activities, or verticalization using crutches or a brace) in F1 injuries is 3-6 weeks based on the age of the patient, it increases with the age, with the minimum being 3 weeks. 7. Duration of spinal load reduction (verticalization using crutches or a brace) in F2 and F3 injuries is 6-12 weeks based on the age of the patient, it increases with the age, with the minimum being 6 weeks. Key words: pediatric spine injury, thoracolumbar compression fractures, children trauma treatment.
Keywords: fraktury páteře; Infant; dítě; předškolní dítě; novorozenec; výsledek terapie; lidé; Infant, Newborn; bederní obratle; Thoracic Vertebrae; Treatment Outcome; kompresivní fraktury; Kyphosis; kojenec; Lumbar Vertebrae; Child, Preschool; Fractures, Compression; hrudní obratle; Child; Spinal Fractures; kyfóza; Humans